Interaksi Farmakokinetika Kombinasi Captopril Dengan Rebusan Daun Sirsak (Annona Muricata L.) Pada Tikus Putih Jantan (Rattus Norvegicus) Galur Wistar - Rina Saputri; Mustaqimah Mustaqimah; Ali Rakhman Hakim (Jurnal Farmasi Indonesia, 2022)
Hypertension is a disease that cannot be cured, but can only be controlled, therefore hypertensive patients must get the treatment for the rest of their life. Currently, the treatment pattern of the community has started to return to using natural ingredients as a therapeutic alternative. The community considers the use of herbal medicines is safe, but actually when the herbal medicines is taken together with synthetic medicines, there are interaction potential that should be monitored. The purpose of this study was to analyze the Pharmacokinetic Interaction of Captopril Combination with Soursop Leaf Decoction. This study was an advanced experimental study with a random block design. The group of test animals was divided into three groups, namely the captopril group, the combination group of captopril and soursop leaf decoction at the same time, and the combination group of captopril and soursop leaf decoction with an consumption interval of 2 hours. The results of the descriptive analysis showed that there were differences in the pharmacokinetic profile of each group. Combination with captopril with soursop leaf decoction is able to increase captopril levels in blood plasma and increase the elimination rate of captopril. However, the statistical analysis showed there is no significant difference.